Postwar artillery 1945-present - Haskew, Michael E. (The essential weapons identification guide, 2011)
The Essential Weapons Identification Guide: Postwar Artillery 1945-Present offers an highly-illustrated guide to the world's main artillery units and their weapons used since the end of World War II